ANALISIS PENGARUH KUALITAS PELAYANAN, KETERSEDIAAN PRODUK, DAN CITRA TOKO TERHADAP KEPUTUSAN PEMBELIAN DI TOKO SPAREPART MOTOR PUTRA LAWU - Rohwiyati, Rohwiyati; Haryono, Tulus; Wahyudi, Lilik; Setiawan, Ahmad Ikhwan (Universitas Of Surakarta, 2024)
This study aims to analyze the influence of service quality, product availability, and store image on purchasing decisions at motorcycle spare parts stores both partially and simultaneously. This research is a quantitative research with survey design. The population in this study is 623 customers of the Putra Lawu store taken from sales data during June – November 2023, while the sample is 86 customers taken using purposive sampling techniques. Data were collected using questionnaires, then analyzed using t-Test, F Test and Coefficient of Determination Test. The results showed that service quality, product availability, and store image on purchasing decisions at motorcycle spare parts stores both partially and simultaneously. This means that when service quality, product availability, and store image are well managed, it positively influences consumer purchasing decisions at the Putra Lawu motorcycle spare parts store. In other words, the combination of these three factors has a strong influence in persuading consumers to choose and make purchases at the store. Therefore, a good understanding and management of service quality, product availability, and store image is very important for a store's success in attracting and retaining customers.